2021
DOI: 10.3389/fonc.2020.610651
|View full text |Cite
|
Sign up to set email alerts
|

P. aeruginosa Mediated Necroptosis in Mouse Tumor Cells Induces Long-Lasting Systemic Antitumor Immunity

Abstract: Necroptosis is a form of programmed cell death (PCD) characterized by RIP3 mediated MLKL activation and increased membrane permeability via MLKL oligomerization. Tumor cell immunogenic cell death (ICD) has been considered to be essential for the anti-tumor response, which is associated with DC recruitment, activation, and maturation. In this study, we found that P. aeruginosa showed its potential to suppress tumor growth and enable long-lasting anti-tumor immunity in vivo. What’s more, phosphorylation- RIP3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, L. interrogans was observed on the surface of neutrophils and not phagocytized whereas L. biflexa was phagocytized ( 26 ) which further shows the importance of these cells in clearance of Leptospira . Here we show that apoptosis and necroptosis of neutrophils only in L. interrogans infected mice suggests that early removal of these cells from the innate immune cell repertoire and the enhanced inflammation promoted by necroptosis ( 29 ) may contribute to L. interrogans evasion, dissemination, pathogenesis and activation of the adaptive immune system characteristic of acute leptospirosis. We speculate that necroptosis may play a role in phagocytosis impairment by neutrophils in the presence of L. interrogans .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, L. interrogans was observed on the surface of neutrophils and not phagocytized whereas L. biflexa was phagocytized ( 26 ) which further shows the importance of these cells in clearance of Leptospira . Here we show that apoptosis and necroptosis of neutrophils only in L. interrogans infected mice suggests that early removal of these cells from the innate immune cell repertoire and the enhanced inflammation promoted by necroptosis ( 29 ) may contribute to L. interrogans evasion, dissemination, pathogenesis and activation of the adaptive immune system characteristic of acute leptospirosis. We speculate that necroptosis may play a role in phagocytosis impairment by neutrophils in the presence of L. interrogans .…”
Section: Discussionmentioning
confidence: 85%
“…The increased expression of the active phosphorylated forms p-MLKL, p-RIP1 and p-RIP3 after pathogenic infection activates the necroptotic complex necessary to initiate the membrane pore formation in those immune cells to release inflammatory arsenals (DAMPs) necessary to maintain an inflammatory milieu and thereby invite the adaptive response which results in aggravated pathogenicity ( 12 ). These biomarkers were also increased in spleen cell lysates stimulated with other pathogens ( 5 , 17 , 29 , 32 ). The spotty increased expression of those key biomarkers at 24h and 72h post infection with the nonpathogenic L. biflexa suggests a discontinuous inflammatory process as the innate response is enough to provide protection.…”
Section: Discussionmentioning
confidence: 92%
“…88 Pseudomonas aeruginosa can trigger robust and durable anti-tumor response by promoting tumor cell death with the secretion of HMGB-1, thereby stimulating DC maturation via TLR4/myD88 signaling and eliciting a longlasting anti-tumor immunity. 89 Additionally, peptidoglycan derived from Lactobacillus paracasei subp. paracasei X12 could induce ICD in colon cancer cell model through the release of HMGB1 and translocation of CRT.…”
Section: Bacteria or Microbial Metabolites Involved In Icd-related Ca...mentioning
confidence: 99%
“…In addition to PA-MSHA, the anti-tumor effects of a clinical isolate of P. aeruginosa strain 1409 were examined in vitro and in vivo by Qi et al. ( 20 ). The authors demonstrated that P. aeruginosa 1409 induced a programmed necrosis (necroptosis) of TC-1 tumor cells through activation of TLR4-RIP3-MLKL, and the HMGB1 released by the dying tumor cells further induced DC maturation and migration to tumor sites.…”
Section: Live Attenuated or Inactivated P Aeruginosa ...mentioning
confidence: 99%
“…The authors demonstrated that P. aeruginosa 1409 induced a programmed necrosis (necroptosis) of TC-1 tumor cells through activation of TLR4-RIP3-MLKL, and the HMGB1 released by the dying tumor cells further induced DC maturation and migration to tumor sites. Subsequently, the mature DC promoted T-cell responses by presenting tumor-associated antigens, thus resulting in remarkable tumor suppression in a TC-1 grafted tumor mouse model ( 20 ). This study indicates that the pathogenic clinical strains of P. aeruginosa could induce a potent anti-tumor response by reshaping tumor microenvironment.…”
Section: Live Attenuated or Inactivated P Aeruginosa ...mentioning
confidence: 99%